Reproducibility and Stability of Aqueous Metabolite Levels in Extracted Serum by NMR Spectroscopy - Miele, Matthew M.; Irving, Brian A.; Wenrich, Broc R.; Martin, Phillip L.; Rovnyak, David (Current Metabolomics, 2017)
Background: Metabolomics offers the potential of correlating a macroscopic view of an organism to measured levels of small molecule reporters of metabolic pathways. Despite strong growth in metabolomics studies, questions on reproducibility and sample stability deserve a closer look. Objective: This work measured acetonitrile extractions of the aqueous components of fetal bovine serum (FBS) by 1H NMR spectroscopy to determine the stability and reproducibility of metabolite levels over time at storage temperatures of 20, 4, -30, and -80 °C. Method: First, mock sera, spiked sera, and pooled human sera were used to find the measurement precision and detection limits of the instrumentation used here (600 MHz, roomtemperature triple resonance probe). Next, using four replicates at each of four storage temperatures, 48 metabolites extracted (2:1 acetonitrile to serum) from FBS samples were profiled over several time scales. Results: Although most metabolites were found to be more stable than expected at room temperature, ca. two weeks, allantoin, creatinine, and glutamine degraded much more rapidly than others at both room temperature and 4 °C, measurably decreasing over a few hours or 1 day, respectively. Storing samples at 4 °C dramatically improves the lifetime of all metabolites, while the fidelity of extracted samples over very long term storage at -30 and -80 °C is supported by this work. Slight degradation of the cryogenically stored serum extracts is linked to freeze-thaw cycles. Conclusion: The poor stability of a few metabolites for short times supports vigilance in minimizing and standardizing room temperature handling and refrigeration of extracted samples, as inconsistent sample storage even on short time scales would introduce variation that would confound clustering.
Keywords: Metabolomics